Coomb’s Test Negative Autoimmune Hemolytic Anemia - Dhakal, Ajaya kumar; Shrestha, Devendra; Shah, Subhash Chandra (Medical Journal of Shree Birendra Hospital, 2015)
Autoimmune hemolytic anemia is uncommon type of anemia in children. High degree of clinical suspicionalong with detailed investigations is required for diagnosis. It is characterized by anemia and positive directantiglobulin test along with features of hemolysis. Infrequently direct antiglobulin test may be negative inautoimmune hemolytic anemia and may pose diagnostic difÞ culty. We report a 14 year-old female with twoacute episodes of severe anemia along with splenomegaly, reticulocytosis, unconjugated hyperbilrubinemia andnegative direct antiglobulin test. She was successfully treated with oral prednisolone. Serum Vitamin B12 levelwas low in this patient and association between autoimmune hemolytic anemia and Vitamin B12 deÞ ciencycould not be explained. doi: http://dx.doi.org/10.3126/mjsbh.v12i2.12930